Bioecology of dominant pest species on ephemeralephemeroid pastures. (Texas Journal of Multidisciplinary Studies, 2021)
The article highlights the results of experiments on researching the bioecological development of dominant pest species in pastures of ephemeral-ephemeroid vegetation in the southern and central regions of the Republic of Uzbekistan.